A case study on needling technique as a treatment for ocular setariasis in eye of a horse - Rahman, Mizanur; Rana, Eaftekhar Ahmed; Tanvir, Mohaiminul Islam; Sabuj, Abdullah Al Momen; Imtiaz, Mohammed Ashif; Hasan, Tanjila (Asian Journal of Medical and Biological Research, 2017)
A 2.5 year old male horse was presented to Teaching Veterinary Hospital, VCRI, Namakkal, India with the history of lacrimation, impaired vision and progressive corneal opacity in left eye. Clinical examination revealed movement of a thread like worm in the anterior chamber of the eye. For removal of the worm, affected eye was prepared for surgery by deep sedation with xylazine hydrochloride. Then general anaesthesia was done with Ketamine hydrochloride and maintained by isoflurane. After induction, worm was removed by needling technique. Topical antibiotic and steroid were administered postoperatively to check secondary bacterial infection and corneal opacity. After surgery, the vision was restored and corneal opacity was reduced gradually. Morphologically, the worm was identified as Setaria spp. This is a common case in India due to vector prevalence. Asian J. Med. Biol. Res. September 2017, 3(3): 398-404